Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Noviditha Sembiring; Adanan Silaban; Halomoan Sihombing (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Competitive advantage can be obtained by using science and technology to learn how to use other resources effectively and economically, thus making intellectual capital a significant asset in today's business world. This study aims to determine the effect of Intellectual Capital (IC) on company performance, especially in manufacturing companies listed on the Indonesia Stock Exchange. The population used was 91 companies and obtained a sample of 39 companies that met the research criteria. This research is a quantitative study with the type of data source is secondary data obtained from financial statements and annual reports which are tested using SPSS software version 27. Based on the results of the study, it is found that company performance as measured using ROE (Return on Equity) only has a positive effect on VAHU (Value Added Human Capital) and STVA (Structural Capital Value Added), while VACA (Value Added Capital Employed) has a negative effect. Suggestions that can be given for further research are to conduct research on a larger population and emphasize the importance of intellectual capital and company management and financial reporting standards.